Effectiveness of Boiling Method Using Aquadest Solvent in Oolong Tea Extraction Producing Mangenese Particle as a Contrast Media on Magnetic Resonance Cholangiopancreatography (MRCP) - Fatimah Fatimah; Neni Susilaningsih; Hermina Sukmaningtyas; Agus Subagio (Medical Laboratory Technology Journal, 2021)
Magnetic Resonance Cholangiography (MRCP) examines the pancreas and ductus billiaris using magnetic resonance imaging with a negative contrast media administered orally. Oolong tea is possible to be an alternative of an oral negative contrast media due to its manganese contained. This study will elaborate on the best method of oolong tea extraction to get the best mangenese substance and its capability to suppress inevitable organs. This is an experimental study with various methods of extraction, which are the maceration method with ethanol solvent, maceration method with aquadest solvent, and boiling method. The whole process includes collecting and preparing plant materials, sample identification, sample processing, extraction, and extract characterization. The manganese level is checked with Atomic Absorption Spectroscopy (AAS) followed by scanning the extracted oolong tea in bottles and MRCP scanning examination. Results showed that manganese level with three different extraction methods is maceration method with ethanol is 1.23 mg/dl, maceration method with aquadest solvent is 0.82 mg/dl, and the extraction using the boiling method with aquadest solvent 0.94 mg/dl, and manufactured tea 1.40 mg/dl respectively. Scanning the extracted oolong tea in bottles showed that the best suppression is on the bottle, which contains extracted oolong tea using a boiling method with aquadest solvent. The image enhancement on MRCP showed that biliary trees are all enhanced using all the extraction methods; however, the best suppression for the stomach and duodenum is using the boiling method with aquadest solvent. The best choice for oolong tea extraction to get the best image to enhance and maximum suppression for disturbing organs is the boiling method with aquadest solvent. For the oolong tea, oral media contrast is to consider the level of manganese substance and its capability to suppress the disturbing organ to provide the best image for MRCP